2021
DOI: 10.1186/s13034-021-00387-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between parental-to-child-Maltreatment and self-reported Generalized Anxiety Disorder symptoms in Pakistani Adolescents

Abstract: Background Parent-to-child maltreatment is considered one of the risk factors for Generalized Anxiety Disorder (GAD) symptoms, but this hypothesis has not been adequately tested in Pakistani settings. Aim This study aimed to examine the association between parent-to-child maltreatment and the risk of developing GAD symptoms among adolescents. Methods The association of none to rare, occasionally, and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Thus, as these children presumably experience fear and anxiety on a regular basis, such an unpredictable environment can cause severe difficulties in emotional and stress regulation. Indeed, research has shown that children that experience maltreatment and bullying are at greater risk of later GAD (Copeland et al, 2013 ; Lakhdir et al, 2021 ). One striking difference between GAD and other anxiety disorders is that individuals with GAD have a large number of worries related to everyday life as opposed to specific ones (Dugas et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as these children presumably experience fear and anxiety on a regular basis, such an unpredictable environment can cause severe difficulties in emotional and stress regulation. Indeed, research has shown that children that experience maltreatment and bullying are at greater risk of later GAD (Copeland et al, 2013 ; Lakhdir et al, 2021 ). One striking difference between GAD and other anxiety disorders is that individuals with GAD have a large number of worries related to everyday life as opposed to specific ones (Dugas et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that reported limitations/concerns, 12 (54.5%) noted that PMKs reporting child maltreatment might be affected by bias. Of these, eight studies indicated recall, denial, distortion, and “wish” biases (i.e., a tendency on the part of the participant for the desired outcome) [ 31 , 33 , 34 , 39 , 40 , 41 , 42 , 43 ], and three stated social desirability bias as the primary concern [ 41 , 43 , 44 ]. Table 7 displays the limitations reported.…”
Section: Resultsmentioning
confidence: 99%